Co-occurring Spirogyra sp. and enrofloxacin stressors interact to alter macrophyte interactions: evidence from a freshwater mesocosm experiment - Yuqing Tian; Cheng Lin; Xu Zhang; Hui Yang; Hongzhi Mao; Heyin Wang; Jiali Chen; Donghai Zhang; Jiangtao Hu; Xusheng Gong; Junyan Wu; Yuying Li; et al. (Aquatic Sciences, 2026)

Lead and other elements in the diet of children (aged 0–7 years) across 20 Chinese provinces at a home-level survey: seasonal variations of element levels and risks in food, urine, and feces in healthy individuals - Maoyuan He; Xiaoping Li; Yu Gao; Pengyuan Jin; Zebo Yang; Jiayi Li; Xuelian Kui; Tunyang Geng; Xueming Zheng; Xu Zhang; Xiangyang Yan (Environmental Monitoring and Assessment, 2026)

Physical Constraints on Future Tibetan Plateau Summer Precipitation: Emergent Relationships and Pareto Optimal Ensembles - Dongheng Li; Sixu Zhang; Xiaofan Lu; Guoxin Chen; Qiong Li; Suonam Kealdrup Tysa (International Journal of Climatology, 2026)
Precipitation projections over the Tibetan Plateau (TP) are critical for regional water resources adaptation and ecological security; however, inter‐model uncertainty substantially constrains their reliability. Based on the Phase 6 of the Coupled Model Intercomparison Project (CMIP6) multi‐model ensemble, this study employs emergent constraint schemes grounded in physical relationships and Pareto optimal ensemble selection schemes based on model screening, aiming to reduce uncertainties in mid‐to‐late 21st century (2051–2100) summer precipitation projections over the TP. The results indicate that inter‐model uncertainty is the dominant source limiting projection robustness, maintaining its leading role throughout the 21st century with a peak contribution during 2040–2050 and remaining significant in the mid‐to‐long term (69%). Emergent constraint relationships of TP summer precipitation with historical global warming trends and with Indo‐Pacific Warm Pool Sea Surface Temperature (SST) are both statistically significant and effectively reduce future projection uncertainty. Using Pareto optimal multi‐objective screening, bivariate constraint schemes pairing summer precipitation with the global warming trend and with Indo‐Pacific Warm Pool SST are found to outperform emergent constraints in compressing uncertainty. Specifically, they reduce uncertainty by more than 30% under the low emission scenario and can reach up to 40% under the medium and high emission scenarios. After constraint application, the projected mid‐to‐long term summer mean precipitation over the plateau converges to 5.77–7.22 mm day −1 , effectively correcting the systematic overestimation present in the original ensemble. Highly consistent spatial patterns across methods enhance projection robustness. Constrained increments show a south to north decreasing gradient, consistently suppressing southern overestimation. Most importantly, the optimal scheme reveals negative precipitation anomalies over the northwestern plateau, suggesting that this region may face a localised aridification risk.

Co-occurrence networks dominated by rare and abundant fungal species influence the potential function of fungal communities in Eucalyptus urophylla plantations under successive planting - Yuting Yang; Aoyu Ling; Lingyue Zhu; Qinzhan Wu; Kangting Huang; Dexu Zhang; Zhengye Wang; Zuoyu Qin; Lichao Wu; Jian Tang (Applied Soil Ecology, 2025)

A multi-biomarker approach to study the toxic effects of thallium on earthworms (Eisenia fetida) fed with different food sources - Shuai Li; Weina Xue; Nan Gao; Xiaoyu Niu; Tiandong Wang; Benteng Zhu; Xu Zhang; Zhifeng Wang (Applied Soil Ecology, 2025)

Soil viruses regulate soil nutrient cycling through themselves and their effects on host functioning to impede the growth of continuously planted Casuarina equisetifolia - Yu-Hua Wang; Lei Hong; Yi Lin; Miao-En Qiu; Jian-Juan Li; Qing-Xu Zhang; Xiao-Li Jia; Yu-Lin Wang; Li-Yuan Wang; Yang-Xin Luo; Wen-Xiong Lin; Hai-Bin Wang; et al. (Applied Soil Ecology, 2025)

Thinning increased the contribution of microbial necromass to the soil organic carbon in shelter forests - Guifang Wang; Ming Hao; Wenli Zhu; Wei Zhao; Xingjian Dun; Zixu Zhang; Qicong Wu; Peng Gao (Applied Soil Ecology, 2025)

Analysis of growth inhibition of continuously planted Casuarina equisetifolia in relation to characteristic soil microbial functions and nutrient cycling - Yu-Hua Wang; Lei Hong; Jian-Juan Li; Qing-Xu Zhang; Ai-Qi Wang; Shao-Xiong Lin; Ming-Yue Hu; Yi-Ling Chen; Wen-Xiong Lin; Hai-Bin Wang; Ze-Yan Wu (Applied Soil Ecology, 2024)

The antiviral activity of currently used medicinal plants in aquaculture and structure–activity relationship of their active ingredients - Yang Hu; Xu Zhang; Li‐peng Shan; Lei Liu; Jiong Chen (Reviews in Aquaculture, 2024)
Aquaculture is an important source of high‐quality protein and plays a crucial role in ensuring global food security. However, viral diseases have caused significant damage to aquaculture production, making it necessary to develop effective measures to treat them. Although drugs are commonly used to treat viral diseases, recent studies have shown that crude extracts of medicinal plants and their active ingredients have potential applications in the treatment of aquatic viral diseases. Furthermore, natural small molecule compounds from herbs could be used as lead compounds to develop more potent anti‐aquatic virus derivatives. As such, there is an urgent need to develop and apply drugs for the treatment of viral disease outbreaks in aquaculture. In this review, we summarize previous studies on the efficacy of different agents used as antiviral drugs in aquaculture, with a focus on their protective effects. Additionally, we highlight the potential of active natural compounds isolated from medicinal plants, which could serve as lead compounds for developing aquatic‐specific drugs. However, the relationship between the structure of a compound and its antiviral activity in aquaculture has not been clearly elucidated, posing a challenge for further drug optimisation. Therefore, this study also analyses the structure–activity relationship of several reported lead compounds and their derivatives in aquaculture, providing a reference for subsequent drug development efforts.